Professional Ethics Of Accountants In Sme Accounting: Practices and Implications - Abdul Fatah Hassanudin; Nurjaman; Iin Srimulyani (Outline Journal of Management and Accounting, 2026)
This study aims to analyze the role of accountants’ professional ethics in the accounting practices of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly in addressing implementation challenges and their implications for financial reporting quality and stakeholder trust. This research employs a qualitative approach using a case study method conducted on MSMEs in Bandung. Data were collected through in-depth interviews, direct observations, and document analysis to obtain a comprehensive understanding of accounting practices. The findings indicate that the application of professional ethical principles, including integrity, objectivity, and confidentiality, contributes significantly to improving transparency and reliability in financial reporting. However, limitations in knowledge, human resources, and accounting systems remain key challenges in their implementation. Therefore, this study recommends the provision of ethics training and the development of simple and applicable accounting systems to enhance the sustainability and accountability of MSMEs.